Systematics and Phylogeny of Leptomorphus Curtis (Diptera: Mycetophilidae) - Borkent, Christopher J.; Wheeler, Terry A. (Zootaxa, 2012)
The world fauna of the genus Leptomorphus Curtis, 1831 is revised and a phylogeny of species relationships, based onmorphological characters, is presented. An updated genus diagnosis and description are given. Species descriptions,diagnoses, illustrations of general habitus, wings, male genitalia and distributions are provided for 37 valid species, alongwith a key to adults.Twelve new species are described; L. amorimi Borkent, n. sp., L. brandiae Borkent, n. sp., L. crassipilus Borkent, n.sp., L. eberhardi Borkent, n. sp., and L. waodani Borkent, n. sp., from the Neotropical realm, L. furcatus Borkent, n. sp.,and L. perplexus Borkent, n. sp., from the Nearctic realm, L. mandelai Borkent, n. sp., and L. stigmatus Borkent, n. sp.,from the Afrotropical realm, and L. tabatius Borkent, n. sp., L. tagbanua Borkent, n. sp., and L. titiwangsensis Borkent,n. sp., from the Oriental realm. Type specimens were studied for all but three species (L. ornatus, L. subforcipatus and L.talyshensis). Leptomorphus elegans Matile and L. lepidus Matile are considered junior synonyms of L. gracilis Matile, n.syns., and L. ypsilon Johannsen is a junior synonym of L. hyalinus Coquillett, n. syn. Lectotypes are designated for L.magnificus (Johannsen), L. neivai Edwards, and L. walkeri Curtis and a neotype is selected for L. bifasciatus (Say). Thisstudy brings the total number of extant Leptomorphus species to 45, including eight, unique (based on figures anddescriptions), recently described Oriental and northwestern Australasian species (Papp & Ševčík 2011), for whichmaterial was unavailable for this study. The phylogenetic analysis in this study supports the monophyly ofLeptomorphus. The western Nearctic species, L. perplexus, is the sister group to the remaining species, which fell intofour major monophyletic species groups (L. ornatus Brunetti group, L. grjebinei Matile group, L. walkeri group, L.furcatus group). The monophyletic relationships within each group are also discussed. The clades found in this study do not support the arrangement of species in to the Leptomorphus subgenera recognized by previous classifications.